Forest canopies as nature‐based solutions to mitigate global change effects on people and nature - Verheyen, Kris; Gillerot, Loïc; Blondeel, Haben; De Frenne, Pieter; De Pauw, Karen; Depauw, Leen; Lorer, Eline; Sanczuk, Pieter; Schreel, Jeroen; Vanneste, Thomas; Wei, Liping; Landuyt, Dries (The Journal of ecology, 2024)
Via sheltering, decoupling and buffering mechanisms, tree canopies have the capacity to mitigate impacts of multiple global‐change drivers on below‐canopy processes and organisms in forests. As a result, canopies have an important potential as nature‐based solution. The optimal combinations of forest canopy structural attributes to jointly mitigate the impacts of multiple global‐change drivers on below‐canopy organisms and processes have received little attention to date. To help solving this research gap, here we review how forest canopies modulate the effects of four important global‐change drivers—climate warming, drought, air pollution and biological invasions—on below‐canopy conditions. Particular attention is paid to mitigating canopy attributes that can be influenced by forest management, including canopy cover, tree species composition and vertical and horizontal structure. Synthesis. We show that the potential of forest canopies to mitigate global‐change effects is highly context‐dependent and that optimal canopy‐based solutions strongly depend on the environmental context and the targeted subcanopy organisms. Hence, holistic approaches, which maximize synergies and minimize trade‐offs, are needed to optimize the solution potential of forest canopies. Overview of the four reviewed global change drivers (warming, drought, air pollution and biological invasions), their interaction with forest canopies, key‐canopy characteristics and sub‐canopy environmental conditions addressed in this mini‐review. Forest elements by macrovector on Freepik.